Synthesis of 1D boron trioxide nanorods via heat treatment of electrospun PVA nanofibers decorated with amorphous boron - Ozcan, Muecahid; Kaya, Cengiz; Kaya, Figen (ELSEVIER, 2023)
Boron trioxide has the highest boron ratio among boron compounds, which is crucial in many applications. In this study, B2O3 was produced for the first time to date in nanorod morphology to facilitate use of onedimensional (1D) B2O3 compounds. The high solubility renders the use of solution-based methods ineffective for the directional growth of B2O3 crystals; therefore, electrospinning was utilized to produce boron-reinforced PVA nanofibers, which were used as precursors for directional growth of B2O3 nanostructures. Nanofibers were annealed to facilitate the growth of square cross-sectional nanorods with a size of less than 100 nm. Synthesized nanorods could produce novel coatings, composites, and high-sensitivity sensors.
Keywords: Boron trioxide; Electrospinning; Nanorods; Elementel boron; Nanofibers; GROWTH; OXIDATION; ARRAYS; Materials Science; Physics